Analysis of the modern development of commercial banks - Karimova A.M.,; Khursanova F.E, (THE INNOVATION ECONOMY, 2026)
This article examines issues related to the reforms that have taken place in the banking sector of the Republic of Uzbekistan. An analysis of the indicators of the number of credit institutions, the average annual growth of assets, the average annual real growth rate of deposits, as well as the analysis of currency policy, the level of dollar ization of the banking sector, was conducted.